CD INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN BERBAHASA BAGI ANAK USIA DINI DI PONOROGO - Ida Yeni Rahmawati (Universitas Muhammadiyah Ponorogo, 2016)
For early childhood learning now starting to grow rapidly. It can be seen from various types of media used by teachers. Teachers in early childhood schools is now quite a lot to convey the material in the classroom by using various methods present, but also did not close the possibility anyone is still using conventional media and methods. This study is essentially focused learning media use interactive CD to improve the language skills of young children. Interactive CD is one medium that is innovative and interesting to be introduced to the children. In the material presented via interactive CD can be made as attractive as possible, through animated pictures funny, folklore that contain a lot of history and interesting musical instruments. The material contained in the Interactive CD also needs to be inserted knowledge, insight, and value of character education in order to improve all aspects of a child's language skills. Thus, through Interactive CD child will feel happy in learning, and not feel bored